Crustal thickness estimates beneath four seismic stations in Ethiopia inferred from p-wave receiver function studies. (February 2019) - Kibret, Birhanu A.; Ayele, Atalay; Keir, Derek
Abstract: Moho depths beneath four stations of the Ethiopian Seismic Station Network (ESSN) are estimated from P-wave receiver functions (RF). We used high quality seismic data recorded at ANKE (Ankober), DILA (Dilla), HARA (Harar) and SEME (Semera) stations for earthquakes located at epicentral distances ranging from 30 to 100° with magnitude mb ≥ 5.5. We applied a frequency domain deconvolution technique to remove source and propagation path effects from the earthquakes waveforms to make the RFs dependent only on the structure beneath the seismic stations. The minimum number of teleseismic earthquakes used is 14 for HARA while the maximum is 39 for SEME station. A linearized-iterative inversion is applied on the generated radial component of the receiver functions to obtain P-wave velocity models beneath the stations. We achieved a reasonably good fit between the observed and synthetic RFs, which demonstrated the high quality of the inversion process. From the obtained models we estimated Moho depths of 26 ± 2 km for SEME, 36 ± 2 km for DILA, 38 ± 2 km for HARA and 42 ± 1.7 km for ANKE. The lowest Moho depth is observed at Semera station which implies a thinned crust while the highest crustal thickness is observed at Ankober, which lies along the North western plateau margin. Our results agree with previous observations which strengthen the hypothesis that Moho depths estimated for stations that lie within the rift and rift margins are lower than those located in the plateaus. Our RFs inversions show a low velocity gradient at about 16 km depth at Semera station, interpreted as evidence for lower crustal storage of partial melt. Highlights: Moho depths for SEME, DILA, HARA and ANKE are 26 ± 2 km, 36 ± 2 km, 38 ± 2 km and 42 ± 1.7 km respectively. Partial melt beneath SEME is sandwiched among cooled magmatic intrusion and anomalous Moho. Moho, has Very low Vp beneath Station SEME, is not in global range and might be named as anomalous Moho. Vp beneath HARA is less heterogeneous. Vp beneath ANKE (7–10 km) is high due to mafic dike intrusion.